PENGARUH KEPATUHAN PERAWAT PADA STANDAR PROSEDUR OPERASIONAL PEMASANGAN VENTILATOR TERHADAP ANGKA KEJADIAN VAP (VENTILATOR ASSOCIATED PNEUMONIA) DI RS PKU MUHAMMADIYAH YOGYAKARTA - Frishia Dida Saraswati (FKU 15 UMY 582, 2015)
Background:Ventilator Associated Pneumonia is defined as nosocomial pneumonia which occurs after 48 hours in patients with mechanical ventilation assistance either through a pipe endotrakel or tracheostomy tube. Ventilator Associated Pneumonia is diagnosed using the Clinical Pulmonary Infection Score. Most of Ventilator Associated Pneumonia in ICU associated with the use of a mechanical ventilator and nursing care that is not right, causing the colonization of bacteria in the oropharynx. Methods:The purpose of this study was to determine the influence of nurse obedience towards Standard Operating Procedure ventilator instalation with the incidence of Ventilator Associated Pneumonia in PKU Muhammadiyah Hospital in Yogyakarta. The method of this research is non-experimental analytic survey research using quantitative and qualitative approaches, the study design with cross sectional method to study the impactofobedience factors and the incidence of a disease. The samples were all nurses and patients with venilator in the ICU of PKU Muhammadiyah Hospital in Yogyakarta. The research instrument using observational sheet of nurse obedience and patient medical records. Result:Based on the results using linear regression test, it can be concluded that there is no significant relationship between nurse obediencewith the score of Clinical Pulmonary Infection Score for diagnosing VAP where the value of p = 0.362 (sig. P <0.05). It might be due to nurse obedience factors can not affect independently the incidence of VAP, but may affect if analyzed with the other factors such as longer installation companion ventilator. The duration of ventilators using would affect on CPIS which is the value of p = 0,000 ( sig . P < 0.05 ) Conclusion: The level of nurse obedience of Standard Operating Procedures Ventilator installation is largely obedience . There is no prevalence of Ventilator Associated Pneumonia in the medical records of patients period from March to May 2015. After analyzed , it can be concluded that there is no influence between scores of nurse obedience with Clinical Pulmonary Infection Score. In this study, it was found that one of the factors that affect the Clinical Pulmonary Infection Score is the duration of the ventilator using.